Forecasting Performance of Indian Non-Life Insurance Industry – An Analysis of Underwriting Experience of Public and Private Insurance Companies - Pal, Subhabaha; Bhattacharjee, Kaushik; Pal, Satyabrata (Asian Journal of Empirical Research, 2017)
This paper is an initial attempt towards the direction of analysis of performances of Indian public and private non-life insurance companies and towards forecasting of future growth potential of the sector. This paper also presents future prospects and growth potentiality of the non-life insurance sector in India along with the current state of the underwriting cycle prevalent in the Indian non-life insurance industry. This paper presents a detailed analysis of the underwriting performance of the non-life insurance sector as a whole during the post-liberalization period of 2000-2001 to 2014-2015. It depicts a colorful prospect for the Indian non-life insurance industry in the next 10 years. This paper has also been devoted to the determination of the presence of an underwriting cycle (pattern) that exists in the performances of the non-life insurance companies (public and private) during the last 15 years.